Study of squamous cell carcinoma associated with syringofibroadenoma for 105 types of human papillomavirus and for all currently known types of polyomaviruses - Fernández-Flores, Angel; Halec, Gordana (Applied immunohistochemistry & molecular morphology, 2014)
Syringofibroadenoma is a benign tumor of the eccrine glands. Few cases of association with squamous cell carcinoma (SCC) have been published in the literature. In one of them, infection by human papillomavirus (HPV) type-107 was detected and the authors postulated that the virus might play a carcinogenic role. We studied a case of syringofibroadenoma associated with an SCC on the back of the right hand of an immunocompetent 95-year-old man. The lesion showed strong diffuse cytoplasmic staining for cytokeratin (CK) AE1/AE3, CK5/6, and 34βE12 in the areas of syringofibroadenoma and in the areas of SCC. The marker p63 was expressed by the lower two thirds of the epithelium of the syringofibroadenoma. Epithelial membrane antigen and CK18 were expressed only by the superficial layers of the syringofibroadenomatous epithelium. The carcinomatous areas were epithelial membrane antigen positive. MIB1, p16, and p53 were mainly expressed by the SCC areas. The lesion was negative for all mucosal and cutaneous genus α-HPV, and for cutaneous HPV from γ-, μ-, and ν-genera. In 3 repeated genotyping experiments analyzing DNA from 2 consecutive biopsy sections, β-HPV-9, 20, 36, 47, and 75, as well as FA-22 and 51 were found only once in the 6 possible reactions. β-HPV-8 and 96 were detected 2 and 4 times, respectively, indicating very low viral loads of these HPV types. None of 8 known polyomaviruses was identified. β-globin positivity was present in each assay, confirming sufficient quality of analyzed DNA.
Received for publication November 5, 2011; accepted December 4, 2011
Gesehen am 30.08.2019